PENGUATAN KARAKTER BELA NEGARA GENERASI MUDA MELALUI WORKSHOP FILM PENDEK - Fajar Edyana; Firdaus Noor; Nuril Ashivah Misbah (Institut Seni Indonesia Surakarta, 2024)
Exactly how nationalism can have a strong influence in films and reflect or reveal a national